Density and extractive potential of “uçá”-crab, Ucides cordatus (Linnaeus, 1763), in mangroves of the “Todos os Santos” Bay, Bahia, Brazil - Mota, Thaís Arrais; Pinheiro, Marcelo Antonio Amaro [UNESP]; Evangelista-Barreto, Norma Suely; da Rocha, Sérgio Schwarz (Elsevier, 2023)
Ucides cordatus is one of the main fishery resources of the “Todos os Santos” Bay (BTS), State of Bahia, Brazil. Population parameters (structure, density, and fishery potential) of this crab species were analyzed in the dry and rainy seasons in nine mangrove areas of BTS. Five sample quadrats (5 × 5 m) were used to record the number and diameter of active open burrows (with biogenic activity) and closed burrows of U. cordatus, tree variables (composition, density, and diameter), and flood level. Crab density (ind.m−2) was indirectly estimated by counting galleries. The diameter of open galleries was converted into carapace width (CW) using a regression model to later characterize the U. cordatus population structure. There were more galleries in the dry season than in the rainy season. Crab density ranged from 0.32 to 2.63 ind.m−2 (1.32 ± 0.90 ind.m−2), and the mean density was higher during the dry period (t = 0.02; p < 0.05). Crab density differed among sampling areas regardless of seasonal period. Crab size (CW) in BTS was 52.4 ± 16.7 mm, with specimens significantly larger during the dry period (t = 0.01; p < 0.05), and there was a significant difference (F = 4.57; p = 000.1) among mangrove areas. Non-commercial size animals (CW < 60.0 mm) were more abundant (65.2%) than those with commercial size (34.8%) in BTS. Crab density and flood level showed significant negative correlation (p = −0.51; p < 0.05), while there was a positive correlation between CW and flooding level (p = 0.40; p < 0.05). U. cordatus population parameters differed significantly among BTS sampling sites due to their heterogeneity. This study is the first assessment of “uçá”-crab populations in BTS mangroves and reveals a need for a sustainable management in the area. Furthermore, this study could be a model for monitoring other large brachyuran species inhabiting estuarine systems, which are economically and biologically relevant.
Keywords: Crustacean; Decapoda; Fishery; Management; Population